2019
DOI: 10.1101/680462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nicotinamide riboside augments the human skeletal muscle NAD+ metabolome and induces transcriptomic and anti-inflammatory signatures in aged subjects: a placebo-controlled, randomized trial

Abstract: Tel: + 44(0)121 414 3917, email: g.g.lavery@bham.ac.uk 26 27 2012), reduction of blood glucose, hepatic steatosis, and neuropathy on high fat diet 64 (Trammell et al. 2016), improvement of cardiac function in genetic cardiomyopathy (Diguet et 65 al., 2018), and prevention of cortical neuronal degeneration (Vaur et al., 2017). Depletion of 66 the enzyme nicotinamide phosphoribosyltransferase (NAMPT), rate-limiting for NAD + 67 biosynthesis, in mouse skeletal muscle severely diminishes NAD + levels and induce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 65 publications
5
16
0
Order By: Relevance
“…The first 31 P-MRS study to report NAD in the aging human brain found that tNAD, NAD + , and the NAD + /NADH redox ratio decreased with age in the occipital region (Zhu et al, 2015). Similar findings were found for NAD + measured by 1 H-MRS (Bagga et al, 2020), but this was not replicated in a recent 31 P-MRS study in which NAD was not affected by age (Elhassan et al, 2019). When NAD was measured in the frontal lobe of healthy participants (Kim et al, 2017), an age-dependent increase in NADH and decrease in the NAD + /NADH redox ratio was observed, but no change in NAD + was detected.…”
Section: Nad Association With Atp Level and The Influence Of Agementioning
confidence: 86%
“…The first 31 P-MRS study to report NAD in the aging human brain found that tNAD, NAD + , and the NAD + /NADH redox ratio decreased with age in the occipital region (Zhu et al, 2015). Similar findings were found for NAD + measured by 1 H-MRS (Bagga et al, 2020), but this was not replicated in a recent 31 P-MRS study in which NAD was not affected by age (Elhassan et al, 2019). When NAD was measured in the frontal lobe of healthy participants (Kim et al, 2017), an age-dependent increase in NADH and decrease in the NAD + /NADH redox ratio was observed, but no change in NAD + was detected.…”
Section: Nad Association With Atp Level and The Influence Of Agementioning
confidence: 86%
“…This decline, exacerbated by COVID-19, might therefore promote hyperactivation of NLRP3 and the trigger cytokine storms in COVID-19 patients [10]. Maintaining NAD + levels may therefore alleviate COVID-19 symptoms, a possibility supported by recent data showing that SARS-CoV-2 proteins hyperactivate poly-ADP-ribose polymerases PARP9, -10, -12, and -14 and deplete cellular NAD + [56] and the ability of NAD precursors to lower inflammation in human subjects [57,58].…”
Section: Increased Inflammation and Cytokine Storms In The Agedmentioning
confidence: 98%
“…Recently, we performed integrative analysis of multi-omics data on different metabolic conditions and found that combined metabolic cofactors supplementation (CMCS) consisting of L-serine, N-acetyl-L-cysteine (NAC), nicotinamide riboside (NR), and Lcarnitine tartrate may be used for treatment of the patients with non-alcoholic fatty liver diseases (11,12). On the basis of this evidence, we conducted an animal toxicity study and a human calibration study with/without supplementation of combined metabolic cofactors, and demonstrated the safety of the CMCS (13).…”
Section: Introductionmentioning
confidence: 99%